Fecal Microbiota Transplant in a Patient Infected with Multidrug-Resistant Bacteria: A Case Report - Gouveia,Catarina (2021)
Abstract: Introduction: There has been a growing interest in fecal microbiota transplantation (FMT) as a way to manipulate gut microbiota, with potential benefit in patients infected with multidrug-resistant (MDR) bacteria. Case Presentation: We present the case of an 87-year-old male with recurrent ascending cholangitis due to biliary atony and impaired biliary drainage after multiple biliary sphincterotomies and two papillary balloon dilations. In this context, a choledochoduodenostomy was performed, but the patient kept on having repeated episodes of acute cholangitis, resulting in multiple hospitalizations, every other week, with need of multiple broad-spectrum antibiotic courses, which led to bacteremias with MDR microorganisms. Several therapeutic strategies such as prophylactic antibiotics (including rifaximin), pre- and probiotics, prokinetics, and ursodeoxycholic acid were unsuccessfully attempted. After multidisciplinary case discussion, an FMT was proposed, with the aim of manipulating gut microbiota and decreasing MDR bacteremias. We first performed FMT via colonoscopy in September 2018, after which the patient still had 3 more hospitalizations for acute cholangitis, but isolated bacteria in blood cultures were resistant only to amoxicillin and clavulanic acid. Considering this apparent change in the microbial resistance profile, we performed a second FMT in January 2019 via the upper gastrointestinal route. During the next 4 months, the patient remained well. In April 2019, the patient relapsed again with three more episodes of cholangitis, for which we repeated the FMT via upper gastrointestinal endoscopy. No readmissions were observed during the next 4 months. All three FMTs were performed without complications. Discussion and Conclusion: FMT seems to be a safe procedure and was effective in decreasing hospital admissions and changing the profile of MDR bacteria previously isolated from blood cultures.